Superstrings in graviphoton background and N = 1/2 + 3/2 supersymmetry - Berkovits, Nathan [UNESP]; Seiberg, Nathan (Springer Nature, 2003)
Motivated by Ooguri and Vafa, we study superstrings in flat ℝ4 in a constant self-dual graviphoton background. The supergravity equations of motion are satisfied in this background which deforms the M = 2 d = 4 flat space super-Poincaré algebra to another algebra with eight supercharges. A D-brane in this space preserves a quarter of the supercharges; i.e. N = 1/2 supersymmetry is realized linearly, and the remaining N = 3/2 supersymmetry is realized nonlinearly. The theory on the brane can be described as a theory in noncommutative superspace in which the chiral fermionic coordinates θα of N = 1 d = 4 superspace are not Grassman variables but satisfy a Clifford algebra. © SISSA/ISAS 2003.
Keywords: D-branes; Superspaces; Superstrings and Heterotic Strings